Relaxation studies on oil, pressboard and oil impregnated pressboard - Cao, Hongyan (2008)
In this thesis, a laboratory relaxation study with FDS and RVM was carried out for a period of 3 years with the fabricated oil (OIL), pressboard (PB), oil-impregnated pressboard (OIP) samples and oil-filled single-phase transformer (SPT). The variation of relaxaton parameters with equilibrium time, temperature change and the added polarizing impurities were studied on individual and composite dielectrics.